Effectiveness of controlling the population of Heracleum sosnowskyi Manden. - Korpita, H.M.; Shuvar, I.A.; Stiurko, M.O.; Kovalchuk, O.I. (Quarantine and plant protection, 2026)
Goal. To evaluate the effectiveness of the application of herbicides and their tank mixtures for controlling the population of Sosnowsky’s hogweed (Heracleum Sosnowskyi Manden.) under the conditions of the Western Forest-Steppe of Ukraine. Methods. The research was conducted during 2021—2025 in the fields of the Educational and Research Center of the Lviv National University of Veterinary Medicine and Biotechnologies named after S.Z. Gzhytskyi. The technical efficiency of herbicides was determined: Roundup Max, SL (potassium salt of glyphosate, 551 g/L), 4.0 L/ ha; Slash, EC (halauxifen-methyl, 5 g/L + clopyralid, 120 g/L), 1.5 L/ha; the tank mixture of herbicides Elumis, OD (nicosulfuron, 30 g/L + mesotrione, 75 g/L), 2.0 L/ha and Roundup Max, SL (potassium salt of glyphosate, 551 g/L), 2.5 L/ ha. Results. The maximum effectiveness of chemical control of Sosnowsky’s hogweed was formed at the cotyledon formation stage. Under these conditions, the level of technical efficiency of the herbicide Roundup Max, SL (4.0 L/ha) was 92.5%, Slash, EC (1.5 L/ ha) — 89.6%, and the application of the tank mixture Elumis, OD (2.0 L/ ha) + Roundup Max, SL (2.5 L/ ha) provided the highest indicator — 98.3%. Up to the stage of eight true leaves, the effectiveness of chemical preparations significantly decreased: in the variant of application of Roundup Max, SL (4.0 L/ ha) it was 39.2%; Slash, EC (1.5 L/ha) — 36.7%; the tank mixture Elumis, OD (2.0 L/ha) + Roundup Max, SL (2.5 L/ha) — 58.9%. Conclusions. The obtained results indicate the presence of a close inverse correlation relationship between the phase of plant development and their sensitivity to the action of herbicides, which is confirmed by a high coefficient of determination (R² = 0.9907). In addition, it was established that in areas infested with Sosnowsky’s hogweed, yield losses of agricultural crops amounted to 25—40%. At the same time, a negative impact of the invasion of Sosnowsky’s hogweed on the biodiversity of plant communities was established: the value of the Shannon index decreased on average by 0.28 relative units, and the Simpson index — by 0.03—0.05.